2012
DOI: 10.1002/jcp.22947
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced delivery of mda‐7/IL‐24 using a serotype chimeric adenovirus (Ad.5/3) in combination with the apogossypol derivative BI‐97C1 (Sabutoclax) improves therapeutic efficacy in low CAR colorectal cancer cells

Abstract: Adenovirus (Ad)-based gene therapy represents a potentially viable strategy for treating colorectal cancer. The infectivity of serotype 5 adenovirus (Ad.5), routinely used as a transgene delivery vector, is dependent on Coxsackie-adenovirus receptors (CAR). CAR expression is downregulated in many cancers thus preventing optimum therapeutic efficiency of Ad.5-based therapies. To overcome the low CAR problem, a serotype chimerism approach was used to generate a recombinant Ad (Ad.5/3) that is capable of infectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…5B). These data are similar to prior studies in prostate cancer cells using the BCL-2 family inhibitor sabutoclax Azab et al, 2012).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5B). These data are similar to prior studies in prostate cancer cells using the BCL-2 family inhibitor sabutoclax Azab et al, 2012).…”
Section: Resultssupporting
confidence: 89%
“…Similar strategies were used to generate Ad.5/3-cytomegalovirus (cmv)-E1A-mda-7 and Ad.5/3-PEG-mda-7. The viruses were expanded and titers determined as previously described elsewhere Dash et al, 2011;Azab et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Level of significance: *P , 0.05; **P , 0.01; ***P , 0.001. et al, 2010b;Azab et al, 2012Azab et al, , 2014. Western blotting showed similar results, with Ad.5/3-mda-7 inducing greater MDA-7/IL-24 protein expression, both with and without the addition of D-limonene compared with Ad.5-mda-7 (Fig.…”
Section: Resultssupporting
confidence: 56%
“…The creation of Ad.5/3 chimeric Ad combines both of these serotypes to create a virus that is capable of using CAR, CD46, and/or desmoglein for infection. We demonstrated that Ad.5/3-mda-7 is able to infect prostate, renal, glioblastoma multiforme, and colorectal cancer cells with greater efficiency compared with Ad.5-mda-7 and that this translates into greater toxicity (Dash et al, 2010b(Dash et al, , 2011Eulitt et al, 2010;Hamed et al, 2010;Azab et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation